Comparative Analysis of Lipids and Fatty Acids in Beaked Redfish Sebastes mentella Travin, 1951 Collected in Wild and in Commercial Products - Svetlana A. Murzina; Viktor P. Voronin; Tatjana R. Ruokolainen; Dmitrii V. Artemenkov; Alexei M. Orlov (Journal of Marine Science and Engineering, 2022)
The lipid and fatty acid profile of muscles in beaked redfish, caught and fixed in the wild versus specimens from food supermarkets (“commercial”), were evaluated, as well as the health implications of this popular food for its consumers based on the calculation of nutritional quality indexes. The contents of the total lipids (TLs), total phospholipids (PLs), monoacylglycerols (MAGs), diacylglycerols (DAGs), triacylglycerols (TAGs), cholesterol (Chol), Chol esters, non-esterified fatty acids (NEFAs), and wax esters were determined by HPTLC; the phosphatidylserine (PS), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylcholine (PC), and lysophosphatidylcholine (LysoPC) were determined by HPLC; and fatty acids of total lipids were determined using GC. The TL content was higher in commercial products due to DA and NEFAs, among PL fractions the content of LysoPC was also higher. The results indicated multidirectional processes of slight degradation of lipids in commercial products in comparison to wild. The flesh lipid quality index was lower due to EPA and DHA in commercial specimens while the index of thrombogenicity was significantly higher. The differences in the quantities of lipid classes between muscle biopsy regions in fish apparently corroborate the morphology and physiology of deep-water fish.